2018
DOI: 10.1111/jcpt.12761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of sodium cantharidinate plus chemotherapy in non-small-cell lung cancer: A systematic review and meta-analysis of 38 randomized controlled trials

Abstract: Current evidence reveals that sodium cantharidinate can improve tumour responses and QOL with a lower risk of haematotoxicity and gastrointestinal toxicity than chemotherapy alone in NSCLC. However, the evidence does not indicate that it can improve long-term survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Aidi injection is composed of cantharidin, astragaloside, ginsenoside, elentheroside E, and syringin (Zhang et al, 2012;Zeng et al, 2016). The results from clinical and basic studies revealed that Aidi has an important antitumor, immunoregulatory, anti-inflammatory and antioxidative stress function (Duan et al, 2018b;Li et al, 2018;Zhou et al, 2018;Xiao et al, 2019a;Chen et al, 2019;Farag et al, 2019;Huang et al, 2019;Li et al, 2019;Qu et al, 2019;Zhang et al, 2019). The results of previous SRs/meta-analyses (Ma et al, 2009;Xiao et al, 2016;Wu et al, 2017a;Xiao et al, 2018a;Xiao et al, 2018b;Wang et al, 2018;Xiao et al, 2019b) demonstrated that Aidi in combination with chemotherapy showed significant improvements in tumor response, QOL, and OS rate, and decreases in ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…Aidi injection is composed of cantharidin, astragaloside, ginsenoside, elentheroside E, and syringin (Zhang et al, 2012;Zeng et al, 2016). The results from clinical and basic studies revealed that Aidi has an important antitumor, immunoregulatory, anti-inflammatory and antioxidative stress function (Duan et al, 2018b;Li et al, 2018;Zhou et al, 2018;Xiao et al, 2019a;Chen et al, 2019;Farag et al, 2019;Huang et al, 2019;Li et al, 2019;Qu et al, 2019;Zhang et al, 2019). The results of previous SRs/meta-analyses (Ma et al, 2009;Xiao et al, 2016;Wu et al, 2017a;Xiao et al, 2018a;Xiao et al, 2018b;Wang et al, 2018;Xiao et al, 2019b) demonstrated that Aidi in combination with chemotherapy showed significant improvements in tumor response, QOL, and OS rate, and decreases in ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SC improved tumor responses and quality of life with reduced risk of hepatotoxicity and gastrointestinal toxicity relative to chemotherapy alone in non-small-cell lung cancer. 18 Moreover, SC possesses the therapeutic ability to lower the expression of S100A3 in hepatocellular carcinoma cells and to induce cellular apoptosis. 19 In the present work, we firstly treated parental and drug resistance cells with SC and provided evidence that SC could remarkably diminish the expression patterns of cancer stem cell markers and spheres formed.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al. ( 35 ) further conducted a meta-analysis of 38 trials involving 2,845 patients in China, and found that SCA could increase the ORR (1.52 [1.40-1.66]), DCR (1.20 [1.16-1.25]) and QoL (1.76 [1.56-1.98]), but not the 1- and 2-year OS rate (1.16 [0.91-1.47] and 1.21 [0.51-2.91], respectively). Subgroup analysis revealed that SCA was associated with a lower risk of nausea/vomiting, gastrointestinal reactions, neutropenia and thrombocytopenia compared with that of chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…(35) further conducted a meta-analysis of 38 trials involving 2,845 patients in China, and found that SCA could increase the ORR (1.52 [1.40-1.66]), DCR (1.20 [1.16-1.25]) and QoL (1.76 [1.56-1.98]), but not the 1-and 2-year OS rate (1.16 [0.91-1.47] and 1.21 [0.51-2.91], respectively).…”
mentioning
confidence: 99%